Healthcare Providers and Patients Perception on Telehealth Services Adoption for Post-Operative Follow-Ups at the Korle Bu Teaching Hospital (Ghana) - Jonathan Kissi; Vivian Kruh; Godwin Adzakpah; Caleb Annobil; Daniel Kwame Kwansah Quansah; Sarkodie Yaw Appiah; Veronica Adwubi; Kerzia Jacobell Owusuwa; Daniel Opare; Joseph Owusu-Marfo (Health Services Insights, 2025)
Introduction: Telehealth is revolutionizing healthcare, particularly in post-operative care accessibility. However, technological limitations, costs, and communication barriers hinder its full implementation. This study examines healthcare providers’ and patients’ perception on telehealth services adoption for post-operative follow-ups at Korle Bu Teaching Hospital (KBTH), Ghana. Methodology: A descriptive cross-sectional study design was employed to collect data involving 350 participants, (doctors (29), nurses (96), and patients (225)) at KBTH’s surgical department using the priori power calculation method. Participants were selected via purposive and convenience sampling. There was a pilot-tested electronic and paper questionnaire administered by trained research assistants. The instrument captured multidimensional perception indices (eg, clinical efficacy, convenience, economic burden) on validated Likert scales alongside socio-demographic and telehealth utilization covariates. Data were managed in REDCap with mandatory fields to minimize missing responses and anonymized identifiers to reduce bias. Analyses comprised descriptive statistics and proportions in IBM SPSS v26 and R v4.2.1. Results: A substantial 76.6% of stakeholders agree or strongly agree that telehealth reliably monitors minor postoperative conditions. Convenience and efficiency are paramount, with 82.9% of participants finding virtual follow-ups more convenient and 86.6% reporting significant time savings relative to in-person visits. Infection-control benefits are widely recognized (85.2%), and patient-provider rapport remains strong, with only 10.9% expressing discomfort. Major barriers include unstable broadband (83.4%), limited on-site technical support (66.0%), poor audiovisual quality (81.7%), and prohibitive data/device costs (61.4%). Key facilitators encompass robust security measures trusted by 73.8% of users, regulatory confidence (59.7%), perceived clinical equivalence (76.5%), and enhanced access for underserved populations (82.6%). Conclusion: Telehealth improves accessibility and efficiency in minor post-operative care. However, addressing technological barriers, insurance issues, and communication challenges is crucial. A hybrid approach integrating telehealth with in-person visits is recommended to enhance care quality and patient satisfaction.